The current LDL-C target <1.4mmol/l of the ESC is achieved in less than 16% of patients with Coronary Heart Disease despite effective lipid-lowering therapy: data from the LLT-R registry. (25th November 2020) - Noack, F; Schwaab, B; Voeller, H; Eckrich, K; Guha, M; Bongarth, C; Heinze, V; Schlitt, A
Abstract: Background: In the current guideline of the ESC, in patients with very high cardiovascular risk such as coronary heart disease (CHD) a treatment target for LDL-C <1.4mmol/l and/or a halving of the initial value are defined. It is unclear whether these treatment targets are achievable with standard therapy including statins and/or ezetemibe. Methods: The primary objective of this prospective, multi-centre register study was the question of the guidance-based adaptation and adherence to lipid-lowering therapy during and after a cardiac rehabilitation in 1, 100 patients with CHD up to 12 months after discharge from the six rehabilitation clinics involved. Patients were included from 2016 to 2018. Results: The median age of the 1, 100 patients was 63.4±10.4 years, the mean BMI was 28.5±4.7kg/m 2, and 24.1% of patients were female. 12.2% were active smokers, 91.6% reported dyslipoproteinemia, 33.9% suffered from diabetes mellitus and 86.5% from hypertension. The majority of patients were included with the main indications NSTEMI (31.6%), STEMI (29.6%) and after CABG surgery (26.4%). The proportion of patients treated with statins was more than 94% when admitted and discharged from the rehabilitation clinic, as well as in 3- and 12-months follow-ups. Approximately 9% of patients were treated with ezetemibe at baseline. On discharge from the rehabilitation clinic 23% of patients were treated with ezetemibe, which remains stable at 3 and 12 months. PCSK9 inhibitors were used in 0.1–0.3% of patients at all times. The adjustment of LLT during three week cardiac rehabilitation resulted in median LDL-C values of 2.27mmol/l (1.80/2.84) at baseline, 1.97mmol/l (1.57/2.47) on discharge (p<0.001 compared to baseline), 1.94mmol/l (1.57/2.49) after three months and 1.94mmol/l (1.53/2.40) after 12 months. The proportion of patients with LDL-C <1.4mmol/l was 9% at baseline, 15.7% on discharge (p<0.001 compared to baseline), 15.6% at three-month follow-up and 15.1% at 12-month follow-up (Figure 1). Discussion: In the context of cardiac rehabilitation, an effective adjustment of LLT is carried out, which resulted in a significant reduction of LDL-C. However, despite a high percentage of patients on statins and ezetemibe, the proportion of patients in the new target range <1.4mmol/l was only achievable in a small percentage and the question arises whether these treatment targets can be achieved without additional administration of PCSK9 inhibitors in majority of patients with CHD. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): This study was supported by an unrestricted grant from Sanofi-Aventis Germany.